Cyber-Terrorism of ISIS and The Challenge Towards Global Security - Margiati, Titis; Qodarsasi, Umi (State Islamic Institute of Kudus (IAIN Kudus), 2022)
Terrorism activities are no longer carried out traditionally, but have adopted a more modern way by utilizing information technology. Terror groups have even launched recruitment and fundraising processes for terrorist activities through electronic media. This paper aims to identify how ISIS uses cyberspace to carry out its acts of terrorism and how global initiatives are to tackle cyberterrorism. This study used a qualitative descriptive approach. This research data was obtained based on a literature review sourced from previous research in the form of journals, books and other scientific works that are relevant to the topic of discussion. The result of this paper is ISIS uses cyberspace for several purposes, including propaganda dissemination, global recruitment, fundraising, publication, attack planning, and other activities to increase its existence. To fights against international terrorism requires counter-terrorism that based on partnership between all levels of governments, communities and the private sectors. In a globalised, interdependent world, our multilateral, regional and bilateral partnerships have proven critical to achieving global security and counter-terrorism objectives. As a commitment to global cyber security, the United Nations builds technical capacity and prepares guidelines for member countries to anticipate crimes in cyberspace, including cyberterrorism.